Massimo Fagioli, l’Analisi collettiva e la sinistra italiana. 1979-2011 - Del Missier, Giovanni (Il sogno della farfalla, 2017)
The article deals about the relationship that took place, both at a theoretical and at a practical level, between Massimo Fagioli, Analisi Collettiva and political representatives from the Italian Left during two precise historical periods of time: from 1979 to 1981 and from 1999 to 2011. After clarifying ontological, anthropological and methodological factors which made this relationship inevitable, the author examines the main political stakeholders, who got involved in it. These were the Italian Communist Party and the daily newspaper “Lotta Continua” during the first period; and the Partito della Rifondazione Comunista and the Radical Party during the second period, when such people as Fausto Bertinotti, Marco Pannella and Emma Bonino played a significant role. By analysing history, the author highlights that which the different people involved shared, meaning the choice of non violence, the idea of equality, and freedom from clerical hegemony; whereas, that which led to the end of this relationship should be found in the contemporary Left’s poor receptivity of the Human Birth Theory, and in particular of its basic atheism.